Modelling cyclic container freight index using system dynamics - Jeon, Jun-Woo (2022)
This paper investigates the cyclical nature of container shipping market represented by a containerized freight index and proposes a predictive cyclical model of the market. In contrast to the traditional spectral analysis (univariate), system dynamics reflect the drivers of the market in both supply and demand side, and therefore, it is a multi-variate system equilibrium approach consisting of various causal spillovers from sub-components of the market. This study is the first to analyze the cycle of container market using system dynamics. By utilizing system dynamics cyclicality approach, one-step ahead predictions are generated for monthly containerized freight index and compared to conventional benchmarks for post-sample validation. Our study can also help policymakers and shipping liners for better management and invest timing of container ship.